CHARACTERISTICS OF FRESHWATER MUSSEL (Pilsbryoconcha exilis) SHELL AS A SOURCE OF HYDROXYAPATITE - Sidauruk, Santhy Wisuda; Sari, N. Ira; Anggraini, Anggi (Politeknik Kelautan dan Perikanan Dumai, 2023)
Mussel shells are shellfish that live in freshwater and have two parts, namely the meat which is used in food and the shell which is still underutilized. Mussel shells (P. exilis) contain calcium and phosphate compounds that have the potential as hydroxyapatite. Hydroxyapatite is the main mineral component of teeth and bones. This study aimed to determine the hydroxyapatite characteristics of mussel (P. exilis) shells. The method in this study was an experiment with a calcination temperature of 700°C which was repeated 3 times and went through 3 stages including 1) sample preparation, 2) calcium oxide powder (CaO) extraction, and 3) hydroxyapatite synthesis with test parameters consisting of yield analysis, Ca and P levels, and functional groups. The hydroxyapatite characteristics of mussel shells were yield of 6.69%; Ca content of 50.13%; P content of 1.60%; hydroxyl groups were detected at wave number 3641.76 cm-1 and 3570.39 cm-1; phosphate group at wave number 1033.89 cm-1; and carbonate group at wave number 1457.28 cm-1; 1448.60 cm-1 and 1419.67 cm-1.